Notice of Annual Meeting Western Society of Malacologists (Hello World!, 1968)
The second annual meeting of the Western Society of Malacologists will be held at the conference grounds at Asilomar State Park, Pacific Grove, California June 18 to 21, 1969. Scientific papers, symposia on related problems, and exhibits will be presented in various fields related to the study of malacology and invertebrate zoology.